Using Hots ( Higher Order Thinking Skills ) to Improve Students Critical Reading In English Class - Arief Rahmadani; Godefridus Bali Geroda; Widi Syahtia Pane (Inquest Journal, 2023)
In language classes, there are several skills that must be mastered by students, especially in English, namely reading ability. Based on the information obtained, there are still many students who experience difficulties in practicing reading or answering reading text questions in English. In this study HOTS (Higher Order Thinking Skills) was used to train and assist students in answering questions on reading texts in English, especially to train students' critical reading. This research was conducted in 2 meetings where the results of the data obtained showed that the use of HOTS had an effect on students' critical reading.